Analysis of The Role of Fintech in Increasing Financial Inclusion in Indonesia - Syam, Nurfadilla; Randy Dwiana, Andi; Aminah, Nur; Nuryanti; Nurpasila (Jurnal Akuntansi Bisnis dan Ekonomi, 2024)
Financial inclusion in Indonesia has witnessed significant progress in recent years, marked by a notable increase in account ownership. Despite this advancement, challenges persist, particularly with the rapid expansion of the fintech industry. This research investigates the role of fintech in enhancing financial inclusion in Indonesia. Employing a qualitative research method, the study utilizes a literature review approach, which involves analyzing relevant theories and data from journals and other pertinent literature. The findings reveal that fintech plays a crucial role in advancing financial inclusion in Indonesia. Specifically, fintech companies are instrumental in implementing digital payment solutions, which are pivotal in reaching previously underserved populations. Furthermore, fintech has facilitated broader access to credit for those who were traditionally excluded from formal financial systems, thereby narrowing the financial gap. Additionally, fintech has significantly contributed to promoting financial literacy and education, equipping individuals with the necessary knowledge to engage with financial services effectively. This has further empowered individuals and small businesses to participate more fully in the economy. The study concludes that while fintech has made substantial contributions to financial inclusion, ongoing efforts are required to address the remaining challenges, including regulatory hurdles and ensuring that all segments of society can benefit from these innovations. Overall, the integration of fintech into Indonesia’s financial landscape holds great promise for further improving financial inclusion, provided that the industry continues to evolve in a way that meets the needs of the diverse population.